LOCAL PUBLIC POLICY PROCESS – A NEW APPROACH BASED ON THE SYSTEM DYNAMICS PRINCIPLES - BACIU, Cristina; RADU, Ioan; ŞENDROIU, Cleopatra (Journal of Advanced Research in Law and Economics, 2017)
Public Policies are logic sequential activities for solving some high priority problems, which are meant to achieve some objectives and obtain some results with limited, well-defined resources. The model used by public administration for elaborating and implementing the public policies is a result-oriented management model. In this model, the monitoring and evaluation phases play a crucial role in measuring and analyzing the results. The results obtained are then compared with the expected results. Public Policies Elaboration is an extremely complicated process, with many actors involved, lots of decisions and links with other public policies already implemented or being implemented. The decisions taken within this process have different results on the people affected by them.